Comparing Chinese state-sponsored media's agenda-building influence on Taiwan and Singapore media during the 2014 Hong Kong Protest. Issue 1 (2nd January 2018) - Zhang, Tianduo; Khalitova, Liudmila; Myslik, Barbara; Mohr, Tiffany L.; Kim, Ji Young; Kiousis, Spiro
Abstract : This empirical study is in the field of mediated public diplomacy. It examines the role of state-sponsored media in international agenda-building during the 2014 Hong Kong Protest. In this study, state-sponsored media are conceptualized as tools used in international political public relations to influence international media coverage. A quantitative content analysis was performed to determine the association of state-sponsored media and agenda-building with news coverage in Taiwan and Singapore. The results showed that state-sponsored media were strongly associated with international news coverage with regard to object salience, attribute salience, and association salience, which indicated potential influence. In addition, the association of Chinese state-sponsored media with news coverage in Singapore was stronger than the association with news coverage in Taiwan, indicating that the influence of agenda-building was moderated by differences between countries and regions. In addition, we presented a message platform matrix and discussed its theoretical and practical significance. This study contributes to the scholarship on governmental strategic communication in the Greater China region by advancing the knowledge about the effectiveness of the Chinese government's external strategic communication efforts in Chinese-speaking regions.